Effect of SVCs on transmission system voltage profile for different static load models - Eminoglu, U; Hocaoglu, MH (Univ West England-Uwe, 2005)
This paper presents effects of shunt var compensation levels on transmission system voltage profile for different types of static load. For different static load types, in which active and reactive power vary with it's terminal voltages as in exponential form, variations of the load voltage for different sizes of shunt capacitors are simulated with a simple two-bus power system using Matlab SimPowerSystems Toolbox. The simulation results are compared with the analytical solution. To keep the load voltage at different levels, the required reactive power for the different load types are analysed.
39th International Universities Power Engineering Conference (UPEC 2004) -- SEP 06-08, 2004 -- Univ West England, Bristol, ENGLAND
Keywords: SVCs; VAr compensation; transmission system and static load models